Kegiatan untuk Mencegah Penularan TB Paru di Wilayah Kerja Puskesmas - Zita Atzmardina; Belva Zefanya; Hadinata Tenggono Putra; Sekar Ayu Wirawan; Vaentzka Sukanto (jurnal ABDIMAS Indonesia, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Indonesia is ranked 2nd in the country with the highest burden of pulmonary TB. In February 2024, the Ministry of Health recorded that TB cases in Indonesia reached 1,060,000 cases and became the highest number ever before. In April 2024 until now, TB ranked 2nd out of 10 most visits to the Health Center, and 95 new cases of pulmonary TB were found throughout January - June 2024. The purpose of this activity is to increase public understanding of TB, risk factors and prevention of TB, cough etiquette, hand washing steps, and proper use of masks in the Health Center work area. Based on the results of initial observations, lifestyle factors play a role in the high number of TB. The results of the intervention showed that 22 participants (88%) obtained a post-test score. ≥70 points and there was an increase in the average pre-test and post-test scores of 52.9%, and 3 random participants were able to practice all three demonstrations correctly. It can be concluded that there is an increase in knowledge about TB, risk factors and prevention of TB, cough etiquette, hand washing steps, and proper use of masks so that it is expected to reduce TB cases in the work area of ​​the Health Center.